2018
DOI: 10.1186/s13039-018-0401-5
|View full text |Cite
|
Sign up to set email alerts
|

13q mosaic deletion including RB1 associated to mild phenotype and no cancer outcome – case report and review of the literature

Abstract: BackgroundThe 13q deletion syndrome is a rare chromosome disorder associated with wide phenotypic spectrum, which is related to size and location of the deleted region and includes intellectual disability, growth retardation, craniofacial dysmorphisms, congenital malformations, and increased risk of retinoblastoma.Case presentationHere, we report on a teenage boy with a mild phenotype characterized by obesity, hyperactivity, dysphagia, dysgraphia, sleep disturbance, and minor dysmorphic features (round face, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Some of the tumours are caused by loss of the long arm of chromosome 13 [9]. is is known as RB1 gene deletion syndrome and apart from retinoblastoma it is characterised by dysmorphia and developmental delay [9].…”
Section: Disease Backgroundmentioning
confidence: 99%
“…Some of the tumours are caused by loss of the long arm of chromosome 13 [9]. is is known as RB1 gene deletion syndrome and apart from retinoblastoma it is characterised by dysmorphia and developmental delay [9].…”
Section: Disease Backgroundmentioning
confidence: 99%
“…Some patients with 13q-syndrome are affected by a mosaic disease and a few cases have been described [ 8 – 11 ]. Bestetti et al reported a patient with mosaic 13q deletion syndrome including RB1 but no retinoblastoma [ 8 ].…”
Section: Introductionmentioning
confidence: 99%